Supporting and inhibiting factors of community based tourism management: A case study of Setanggor Village - Muhammad Johari; Muhammad Azizurrohman; Yusuf Setiawan Al-Qusyairi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
The development of community-based tourism has developed quite rapidly. Indonesia is one of the countries that have the potential to develop community based tourism by promoting local culture. Setanggor Village is a tourist village that uses the concept of community-based tourism. Thus, the author wants to know more about Community Based Tourism (CBT) management and the supporting and inhibiting factors of Community Based Tourism (CBT) management in the Setanggor tourist village. Using observation, interview, and documentation techniques, the authors found that the people of Setanggor Village are involved in controlling, managing, and developing tourism. In terms of supporting factors, the village government has quite a lot of development funding assistance. In addition, the village community is quite active in tourism development. However, the social status between communities and the bureaucracy of village organizations became the main problems found.